2008
DOI: 10.1002/qre.965
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing tape‐burnishing/wiping process of magnetic recording media through Taguchi method

Abstract: For the ever-increasing recording density in hard disk drives, ultra-low gliding height media are required. It is an immense challenge for the tape-burnishing/wiping process of media to reduce the asperities effectively and efficiently while no scratches occur. The purpose of this paper is to characterize and then optimize the tapeburnishing/wiping process as so to minimize the asperities without leaving any scratches on the media surface. A Taguchi experiment design method is adopted to analyze the data and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The ball burnishing process was carried out on Al-6061 under different levels of control parameters and different burnishing orientations viz. parallel and cross-burnishing orientations by N. S. M. El-Tayeb et al [5]. The results indicated that the burnishing speed of 330 rpm and burnishing force of 160 N produced best responses.…”
Section: Figure 1 Schematic Representation Of Burnishing Processmentioning
confidence: 96%
“…The ball burnishing process was carried out on Al-6061 under different levels of control parameters and different burnishing orientations viz. parallel and cross-burnishing orientations by N. S. M. El-Tayeb et al [5]. The results indicated that the burnishing speed of 330 rpm and burnishing force of 160 N produced best responses.…”
Section: Figure 1 Schematic Representation Of Burnishing Processmentioning
confidence: 96%